Value Chain Analysis of Input Delivery System for Liquid Milk in Bengaluru Milk Union of Karnataka - M, Vanishree; R, Sendhil; Sirohi, Smita; Chauhan, A.K.; HM, Rashmi; K, Ponnusamy (Indian Journal of Dairy Science, 2018)
Dairy cooperative societies play a significant role in delivering inputs like cattle feed, fodder, vereniary and extension services to enhance effiecency in dairying.Â A study was conducted in Bengaluru Milk Union (BAMUL) of Karnataka to know the different types of inputs and services deliverd by the dairy cooperatives and contraints faced by the milk producers in getting the inputs and services. Tabular analysis and Garrettâ€Ÿs ranking technique was used respectively to analyse the input delivery system and constraints at the milk producers level. The study revealed that milk union provides various technical input and extension services like veterniary services, artificial insemination services, vaccinations, balanced cattle feed, fodder seed, mineral mixture, clean milk production practices, extension services for cattle feeding, breeding, and insurance. The union also provides various subsidies or incentives to milk producers in order to enhace the milk production. The study identified that higher transportation charges in getting the inputs from market and delay in input delivery especially green fodder seeds as major constraints faced by the farmers with a Garrett mean score of 83.41 and 59.4, respectively. The study conclude that the milk union should develop new sustainable small scale producer linkage models for providing dairy services and inputs in all season in order to reduce the cost of milk production, transaction cost and constraints of labour, feed access to small holder dairy farms to strengthen the input delivery system along the liquid milk value chain.